The unique continuation property for a nonlinear equation on trees - del Pezzo, Leandro Martin (2014)
In this paper, we study the game p-Laplacian on a tree, that is, u(x) = α / 2 max y∈S(x) u(y) + min y∈S(x) u(y) + β m y∈S(x) u(y);here x is a vertex of the tree and S(x) is the set of successors of x. We study the family of the subsets of the tree that enjoy the unique continuation property, that is, subsets U such that u |U = 0 implies u ≡ 0.